Configurations of Adolescents' Peer Experiences: Associations With Parent–Child Relationship Quality and Parental Problem Behavior - Kretschmer, Tina; Sentse, Miranda; Meeus, Wim; Verhulst, Frank C.; Veenstra, René; Oldehinkel, Albertine J. (Journal of Research on Adolescence, 2016)
Adolescents' peer experiences embrace behavior, relationship quality, status, and victimization, but studies that account for multiple dimensions are rare. Using latent profile modeling and measures of peer behavior, relationship quality, peer status, and victimization assessed from 1,677 adolescents, four profiles were identified: High Quality, Low Quality, Low Quality Victimized, and Deviant Peers. Multinomial logistic regressions showed that negative parent–child relationships in preadolescence reduced the likelihood of High Quality peer relations in mid-adolescence but only partly differentiated between the other three profiles. Moderation by gender was partly found with girls showing greater sensitivity to parent–child relationship quality with respect to peer experiences. Results underline the multifaceted nature of peer experiences, and practical and theoretical implications are discussed.
CRIS-Team Scopus Importer:2025-03-19